USE OF PHYTOTHERAPY IN THE TREATMENT OF MENTAL ILLNESSES ON THE EXAMPLE OF BIPOLAR DISORDER - Tiupova, Тетяна; Tkaczenko, Галина; Kurhaluk, Наталія (Biota. Human. Technology, 2023)
Purpose. Bipolar disorders are among the major health problems that exist worldwide. Bipolar disorder is a psychopathological disease manifested by sudden changes in mood and alternating bouts of mania and depression. They cause significant disturbance to the life quality and social functioning of the affected persons. Synthesized pharmaceuticals have been in use for decades to treat both mood disorders and depression, but despite their efficiency, their use is limited by numerous side effects. Studies to investigate the potential effects of medicinal plants acting on the nervous system and used to treat bipolar disorders are increasingly growing. This review highlights the antidepressant activities of herbals, with a particular focus on the treatment of bipolar disorders. Methodology. This study is based on a literature review conducted through the search of relevant keywords in databases, i.e. Web of Science, Scopus, PubMed, Allied and Complementary Medicine, Embase, and Cochrane databases, and Google Scholar. Six plants were selected based on defined selection criteria for their that are used to reduce the symptoms of bipolar disorder. Scientific novelty. In this review, we presented the antidepressant effects of 6 plant species, with a particular focus on the treatment of bipolar disorders. Emphasis is placed on the pharmacological properties and active substances of the listed medicinal plants (valerian, lemon balm, passionflower, ginkgo biloba, St. John's wort, kava, etc.). Conclusions. Six plants were selected based on defined selection criteria for their that are used to reduce the symptoms of bipolar disorder. The detailed analysis of the research studies revealed that among the herbal preparations that are used to reduce the symptoms of bipolar disorder, it is possible to note valerian, lemon balm, passionflower, ginkgo, St. John's wort, kava, etc. This review, therefore, provides an overview of the work done on botanicals for bipolar disorders.